Grafting efficiency of lignin-grafted-polyacrylic acid - Azhar, Nur Amalina (2015)
Agriculture biomasses have been successfully converted into value-added products such as biocomposite plastics, furniture, papers and textiles. However, only the cellulose parts of these lignocellulosic materials are being used while other components such as lignin and wax are discarded. For a tropical country like Malaysia, banana stem is one of the sources of biomasses. Like other biomasses-based products, only cellulose part of banana stem is used while the lignin portion is discarded due to overly hydrophilic character. This water-loving property of lignin can be manipulated into specific application such as water absorbent for waste treatment. This research is aimed to synthesis water absorbent-based lignin from banana stem. The lignin had been extracted from banana stem using Kraft process prior to grafted with acrylic acid monomer (AA) in order to increase its water absorbency. The reaction was carried out via free radical polymerization in the presence of hydrogen peroxide (H2O2) as initiator and ammonium iron (II) sulfate hexahydrate as catalyst. The reaction temperature was set at 60°C. Grafting efficiency of polyacrylic acid (PAA) onto lignin backbone was determined by varying the amounts of AA monomer, lignin and initiator. The highest grafting percentage was acquired at 60% with the amount of 6ml acrylic acid, 2ml initiator and 0.2g lignin respectively.